Financing from Family and Friends - Samuel Lee; Petra Persson (Research Institute of Industrial Economics (IFN), 2012)
The constraint on informal finance is commonly taken to be high costs and limited supply. But the majority of informal investors family and friends is often willing to supply funds at negative returns, and yet many borrowers tap family and friends only as a last resort. We explain this paradox with a theory based on altruistic ties between the entrepreneur and his family and friends, and propose an alternative explanation of the limits of informal finance: Altruistic ties reduce agency problems in financing. But such ties also increase the entrepreneurs aversion to failure. This makes financing from family and friends unattractive, and undermines the entrepreneurs willingness to take risks. Altruistic ties thus constrain growth even though they relax financing constraints. We relate this insight to the limited success of group-based microfinance in generating entrepreneurial growth. Our theory underscores the value of impersonal transactions, and implies that even counterparties with social ties benefit from formal contracts and third-party intermediation. This sheds light on social-formal financial institutions, such as community funds, crowd funding, and social lending intermediaries.
Keywords: D19; D64; G21; G32; O16; O17; 330; Informal finance; Family loans; Social ties; Altruism; Peer-to-peer lending; Small business